THE STUDY AND ANALYSIS OF SPORT EXPERTS: A PSYCHOLOGICAL APPROACH - Ruiz, Luis Miguel; Sánchez, Mauro; Durán Piqueras, Jesús; Jiménez, Concepción (Anales de Psicología / Annals of Psychology, 2006)
The interest for expertise and expert performance has increased during the last decade from a psychological point of view. Many approaches, methods and theories have been used to study expertise in high level sport. This article made an analysis of these different approaches and proposes a characterization of expert athletes from a perceptive-cognitive, emotional, psychosocial and deliberate practice dimensions. Authors conclude in the necessity of studying sport expertise from a multitask and multidimensional approach.